MISS QUEEN DALAM PANDANGAN TEOLOGI AHLUS SUNNAH WAL JAMA’AH - Tri Yuliana Wijayanti; Ferki Ahmad Marlion (JURNAL AL-AQIDAH, 2022)
The development of LGBT in Indonesia is getting more and more prominent. LGBT people began to dare to use various ways to show the existence of their group by continuing to exist by organizing various activities, one of which was through organizing a very lively beauty contest specifically for transgender people (waria) both at national and international levels under the name Miss queen. The existence of positive appreciation and praise for the implementation of the contest shows that Indonesian citizens, who are majority adherents of Ahlus Sunnah Wal Jama'ah Islam, are starting to accept this deviant phenomenon. Through a sociological approach, the researcher tries to reveal how Miss queen is from the theological view of Ahlus Sunnah wal Jama'ah. The researcher found that in the theology of Ahlus Sunnah wal Jamaah, it is firmly stated that LGBT is categorized as a despicable act and it is forbidden for its adherents to promote, support, and campaign for LGBT activities, including Miss queen.